Development of an information and software model of a specialized concrete work flow to ensure the continuity of the production cycle - Fakhretdinov, Aidar Ramilevich; Sultanova, Ekaterina Aleksandrovna (Программные системы и вычислительные методы, 2022)
Abstract The subject of the study is the process of automating the calculation of the parameters of the design of the technology of concrete works and the justification of the "standard set" of equipment for the organization of a specialized flow of concreting of a typical floor. The transport-concrete cycle is a synchronized schedule of works of the production cycle for laying concrete mix and the dynamics of the ABS kit movement, ensuring the continuity of concreting, through the use of the selected technological scheme of concreting. It determines the continuity of the technological processes of laying the concrete mixture, based on the requirements of mandatory compliance with the concreting time and reducing the number of technological and organizational interruptions of the parameters of the complex process. Thus, the automation of the presented techniques will significantly facilitate the calculation of the total duration of the construction of the monolithic part of the building and ensure the continuity of work on the construction site The scientific novelty lies in the development of a new information system that will allow calculating organizational and technological parameters. The specialized flow of monolithic concrete works consists of reinforcement, concrete and formwork works taking into account architectural planning, structural and technological factors of the designed buildings and structures. For its successful organization, it is necessary to have a "standard set" of equipment and tooling for the manufacture of reinforcement products, formwork systems and the preparation of commercial concrete mixtures. For a simpler calculation of the total duration of the construction of the monolithic part of the building and uninterrupted operation on the construction site, it was proposed to automate the methods of organization, planning and management of construction.